Influence of different freezing modes on the base slab displacement of an upper structure - Wang, L.; Wang, Y.; Li, F.; Liu, Z.; Lu, Chunsheng (MDPI, 2020)
The high risk of metro tunnels that are underneath buildings in a water-rich layer has received much attention. The base slab of an upper structure deforms due to frost heave and settlement, which needs to be predicted before freezing and excavation. In this paper, simulation experiments with a similarity ratio of 1/25 were performed based on an engineering project where two tunnels underpass a running station through an artificial ground freezing method. The displacement of upper structures was analyzed under simultaneous and sequential freezing modes, with a simple formula proposed to estimate the frost heave in closely underpassing projects. It is shown that, under freezing and excavation stages, the base slab displacement displays a zigzag shape. These results are instructive to the construction of underpassing projects in a water-rich layer.